Bismuth chalcogenide compounds Bi2×3 (X=O, S, Se): Applications in electrochemical energy storage. (April 2017) - Ni, Jiangfeng; Bi, Xuanxuan; Jiang, Yu; Li, Liang; Lu, Jun
Abstract: Bismuth chalcogenides Bi2 ×3 (X=O, S, Se) represent a unique type of materials in diverse polymorphs and configurations. Multiple intrinsic features of Bi2 ×3 such as narrow bandgap, ion conductivity, and environmental friendliness, have render them attractive materials for a wide array of energy applications. In particular, their rich structural voids and the alloying capability of Bi enable the chalcogenides to be alternative electrodes for energy storage such as hydrogen (H), lithium (Li), sodium (Na) storage and supercapacitors. However, the low conductivity and poor electrochemical cycling are two key challenges for the practical utilization of Bi2 ×3 electrodes. Great efforts have been devoted to mitigate these challenges and remarkable progresses have been achieved, mainly taking profit of nanotechnology and material compositing engineering. In this short review, we summarize state-of-the-art research advances in the rational design of diverse Bi2 ×3 electrodes and their electrochemical energy storage performance for H, Li, and Na and supercapacitors. We also highlight the key technical issues at present and provide insights for the future development of bismuth based materials in electrochemical energy storage devices. Graphical abstract: Highlights: Discuss current challenges and solutions to develop Bi2 X3 electrode material. Provide an overview of design and application of diverse Bi2 X3 electrodes. Outlook future approaches and pathways to address challenges.